Comparative Analysis of Economic Indicators during the Initial Years of Indonesian Presidential Leadership - Hendi Setiawan; Tri Lestari; Okta Eka Putra (Fakultas Ekonomi dan Bisnis, Universitas Jenderal Achmad Yani, 2026)
This study aims to analyze differences in Indonesia’s macroeconomic performance during the first year of the administrations of President Susilo Bambang Yudhoyono, Joko Widodo, and Prabowo Subianto. The macroeconomic indicators examined include Inflation, Jakarta Composite Index (IHSG) return, Rupiah Exchange Rate against the US Dollar, BI Rate, and Economic Growth (GDP). This research employs a quantitative method with a comparative research design, using monthly secondary data obtained from Statistics Indonesia, Bank Indonesia, and the Indonesia Stock Exchange. Data analysis is conducted using Repeated Measures ANOVA for variables that meet parametric assumptions and the Friedman test for variables that do not meet normality assumptions. The results indicate significant differences in inflation, BI Rate, and GDP across the three government periods. In contrast, IHSG return and the exchange rate do not show significant differences. These findings suggest that macroeconomic conditions in the first year of government are more strongly influenced by global economic factors and policy responses than by changes in national leadership. This study provides empirical insight into Indonesia’s macroeconomic dynamics across different administrations.